MENYOAL KREATIFITAS REDESAIN KEMASAN TRADISIONAL INDONESIA - Lukitasari, Evelyne Henny (KEMADHA, 2012)
Packaging design not only serves as a wrapper but also as a medium for the promotion of a product through a visual language that  promotes  creativity  as  a  weapon  in  creating  his  works. Creativity  in addition  to helping create beautiful work, a new, unique but able to provide solutions to the needs of society in a culture contemporaries. This is intended to revitalize traditional packaging  marginalized  into  the  packing  has  a  sale  value, competitiveness with modern packaging and has prestige.